Transhumanism, Sport, and Technology: Contemporary Tensions on the Limits of the Body (PerCursos, 2025)
This article explores transhumanism as a promise to overcome the limitations of the human body. The foundations of this philosophical movement are analyzed through the lens of René Descartes' philosophy, particularly the mind-body dualism reinforced by mercantile society. Next, the world of high-performance sports is examined as a vehicle for disseminating transhumanist ideals, given its emphasis on pushing the boundaries of biological endurance. Finally, the potential benefits and risks of a transhumanist society are discussed, based on the framework established throughout the analysis.
Keywords: transhumanism; body; technologies; high-performance sports